Power Dynamics in War Reporting: Interrelations Between Local Producers and German Correspondents Covering the War in Ukraine - Hanna Blume; Leonie Götz; Pauline Hille; Anna Kushnir; Luca Lang; Lene Rügamer (Global Media Journal: German Edition)
Russia’s war of aggression against Ukraine underscores the crucial role of local producers in war reporting. This study examines the power dynamics between local producers and German foreign correspondents covering the war in Ukraine. Drawing on ten qualitative, semi-structured interviews with members from both groups, this article employs a field-theoretical approach to analyse mutual expectations, power asymmetries, and their reflection. It particularly focuses on how role perceptions, professional identities, and journalistic practices are negotiated under wartime conditions. The findings reveal a complex network of relationships: while foreign correspondents retain ultimate editorial authority, they simultaneously rely on the cultural capital and expertise of local producers. This interdependency creates a tension between professional collaboration and structural inequality. Foreign correspondents rarely engage in critical reflection on these hierarchies, whereas some local producers actively seek to improve their professional standing – whether through individual professionalisation efforts or collective initiatives such as unionisation. This study highlights the often-overlooked role of local producers in international war reporting and calls for a critical reassessment of existing power structures.